2015
DOI: 10.1160/th14-11-0967
|View full text |Cite
|
Sign up to set email alerts
|

A complementary role for tetraspanin superfamily member CD151 and ADP purinergic P2Y12 receptor in platelets

Abstract: P2Y12 receptor is required for sustained activation of integrin αIIbβ3, irreversible platelet aggregation and thrombus stabilisation. Tetraspanin superfamily member CD151 associates with integrin αIIbβ3 and plays critical roles in regulation of thrombus growth and stability in vivo. The possible functional relationship between P2Y12 and CD151 in a molecular cluster in platelets may affect thrombus formation. Hence our aim was to investigate the physical and functional requirements for this association in plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Impaired platelet aggregation and platelet spreading on fibrinogen, delayed kinetics of clot retraction, restricted cytoskeletal reorganization. Increased bleeding time and volume and rebleeding, but without spontaneous bleeding complications[150, 156, 157]CEACAM-1NullEnhanced aggregation, enhanced platelet adhesion on type I collagen but not fibrinogen, elevated granule secretion, larger and more stable thrombi[137]CIB1Normal soluble fibrinogen bindingNormal aggregation and α-granule secretion, increased tail bleeding time and rebleeding, formation of unstable thrombi, impaired spreading on immobilized fibrinogen, reduced tyrosine phosphorylation of the integrin β3 tail[93, 101]cPLA2αImpaired fibrinogen binding in response to CRP or the lower concentration of PAR4 peptideImpaired collagen-induced aggregation, spreading on fibrinogen, platelet aggregation. Prolonged bleeding time[224, 225]Dab2Impaired soluble fibrinogen bindingSelectively defective in thrombin-induced aggregation, platelet spreading on fibrinogen and clot retraction.…”
Section: Integrin αIibβ3 Outside-in Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired platelet aggregation and platelet spreading on fibrinogen, delayed kinetics of clot retraction, restricted cytoskeletal reorganization. Increased bleeding time and volume and rebleeding, but without spontaneous bleeding complications[150, 156, 157]CEACAM-1NullEnhanced aggregation, enhanced platelet adhesion on type I collagen but not fibrinogen, elevated granule secretion, larger and more stable thrombi[137]CIB1Normal soluble fibrinogen bindingNormal aggregation and α-granule secretion, increased tail bleeding time and rebleeding, formation of unstable thrombi, impaired spreading on immobilized fibrinogen, reduced tyrosine phosphorylation of the integrin β3 tail[93, 101]cPLA2αImpaired fibrinogen binding in response to CRP or the lower concentration of PAR4 peptideImpaired collagen-induced aggregation, spreading on fibrinogen, platelet aggregation. Prolonged bleeding time[224, 225]Dab2Impaired soluble fibrinogen bindingSelectively defective in thrombin-induced aggregation, platelet spreading on fibrinogen and clot retraction.…”
Section: Integrin αIibβ3 Outside-in Signalingmentioning
confidence: 99%
“…Studies using murine CD151 −/− platelets have demonstrated that deletion of CD151 is capable of inhibiting the outside-in signaling properties of αIIbβ3, including reducing agonist-induced platelet aggregation, delaying clot retraction, diminishing platelet spreading on fibrinogen, and reducing formation of filopodia. However, CD151 −/− platelets display normal αIIbβ3 inside-out signaling properties, as evidenced by standard agonist-induced binding of soluble fibrinogen or JON/A antibody [150, 156, 157]. Recent studies by Orlowski et al that used three different models for thrombus formation have confirmed that platelet CD151 is required for regulating thrombus formation in vivo [149].…”
Section: Integrin αIibβ3 Outside-in Signalingmentioning
confidence: 99%
See 1 more Smart Citation